CGIAR Bruce Campbell talks about climate change, food security and a vision of the future - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
CGIAR Climate Program Director Bruce Campbell talks about climate change, food security and a vision of the future. This talk was first prepared for a side-event on 'food security in a changing environment' hosted by the African Development Bank. The talk was delivered by Dr. Robert Zougmoré, West African Regional Program Leader of CCAFS.